(untitled) (Journal of Current and Advance Medical Research, 2015)
Background: Ovarian tumour is a leading cause of morbidity and mortality. Objective: The purpose of the present study was to observe the socio-economic conditions of the ovarian tumour patients. Methodology: This was a cross sectional observational study and was carried out in the Department of Obstetrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital, Dhaka from July 2008 to December 2008. Patient admitted in the Obstetrics and Gynaecology ward in BSMMU hospital with diagnosis as ovarian tumour were selected as study population. Woman suffering from ovarian tumour who were diagnosed by history, clinical presentation, laboratory finding’s and finally, confirmed by operative findings and histopathological report were included in this study. Result: Out of total 382 patients admitted with different gynaecological problem into BSMMU Hospital, 50 (13.09%) were diagnosed as ovarian tumour. Out of 50 patients maximum number of patients belonged to age group 21-30 years (32%). Mean age 38.2±7.31 years with a range 16 to 69. Among the 50 patients 4% of patents belonged to upper class, 56% middle class and 40% were to lower class. Out of total 50 cases 8% were unmarried and 92% were married, of whom 12% were nuliparous and 80% were parous. Conclusion: In conclusion the ovarian tumours are most commonly occurred in middle aged women in the middle income group. The parous women are most commonly suffering from ovarian tumour. Journal of Current and Advance Medical Research, 2015;2(2):39-41